Aircraft pavement design proceedings of the symposium - Hurrell, M. Lyndsay (Institution of Civil Engineers, 1971)
With airport design and construction continuing to be a challenge to civil engineers, these proceedings contribute to the sharing of knowledge necessary for the development of technical improvements.